2010
DOI: 10.1038/nature08858
|View full text |Cite|
|
Sign up to set email alerts
|

Proviral silencing in embryonic stem cells requires the histone methyltransferase ESET

Abstract: Endogenous retroviruses (ERVs), retrovirus-like elements with long terminal repeats, are widely dispersed in the euchromatic compartment in mammalian cells, comprising approximately 10% of the mouse genome. These parasitic elements are responsible for >10% of spontaneous mutations. Whereas DNA methylation has an important role in proviral silencing in somatic and germ-lineage cells, an additional DNA-methylation-independent pathway also functions in embryonal carcinoma and embryonic stem (ES) cells to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
846
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(931 citation statements)
references
References 34 publications
54
846
1
1
Order By: Relevance
“…TRIM28 induces the heterochromatinization of this sequence by recruiting H3K9 di-and trimethylation, HP1 and the NuRD histone deacetylase complex (Sripathy et al, 2006). It was recently shown that TRIM28 also binds to the 5 0 sequence of endogenous LTR-retrotransposons in ES cells and early embryos, and induces their repression in conjunction with ESET-dependent H3K9 trimethylation (Matsui et al, 2010;Rowe et al, 2010). Interestingly, although reactivated IAP sequences lose H3K9 trimethylation and gain H4 acetylation, they still harbor a normal level of DNA methylation in TRIM28-deficient cells.…”
Section: Learning From Infectious Retrovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…TRIM28 induces the heterochromatinization of this sequence by recruiting H3K9 di-and trimethylation, HP1 and the NuRD histone deacetylase complex (Sripathy et al, 2006). It was recently shown that TRIM28 also binds to the 5 0 sequence of endogenous LTR-retrotransposons in ES cells and early embryos, and induces their repression in conjunction with ESET-dependent H3K9 trimethylation (Matsui et al, 2010;Rowe et al, 2010). Interestingly, although reactivated IAP sequences lose H3K9 trimethylation and gain H4 acetylation, they still harbor a normal level of DNA methylation in TRIM28-deficient cells.…”
Section: Learning From Infectious Retrovirusesmentioning
confidence: 99%
“…As a result of the diversity and redundancy of histone-modifying enzymes, the importance of these marks is difficult to assess functionally. Decreases in H3K9 methylation levels through inactivation of H3K9 methyltransferases have variable outcomes on TE silencing in mouse ES cells: inactivation of ESET leads to a robust reactivation of a range of LTR-retrotransposons (Matsui et al, 2010), Suv39h deficiency induces a modest IAP reactivation (Martens et al, 2005), while inactivation of G9a has no effect (Dong et al, 2008). Reduction in H4K20 methylation through Suv420h1 and Suv420h2 deficiency does not affect TE expression in ES cells (Matsui et al, 2010).…”
Section: Host Responses To Tes or How To Live With A Herd Of Squattersmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar phenomenon may be occurring with H3K9me3. While studies have indicated that H3K9me2/3 is required for the maintenance of DNA methylation 44 and participates in the direction of DNMT1 during replication, 48 recent work has demonstrated that H3K9me3 and DNA methylation generally repress distinct sets of genes. 49 That DAC-induced loss of H3K9me3 from repressed areas often leads to its replacement by H3K27me3 9 suggests that the relationship between H3K9me3 and remethylation rate may be indirect, and a function of the accumulation of H3K27me3 in hypomethylated regions.…”
Section: Discussionmentioning
confidence: 99%
“…The first reports at direct reprogramming employed Moloney-based retroviral vectors that are known to undergo silencing in the ESC state (Takahashi and Yamanaka, 2006;Takahashi et al, 2007;Yu et al, 2007); this self-silencing property provided an advantage for initial attempts as the temporal requirement of factor expression, which was defined that proviral silencing in embryonic stem cells requires the histone methyltransferase Eset (Maherali and Hochedlinger, 2008;Matsui et al, 2010). There are several drawbacks for the genome integration system for example their infectivity is limited to dividing cells, thus restricting the range of cell types that can be reprogrammed; silencing occurs gradually during the course of iPSC induction, resulting in a lowered efficiency of conversion compared to nonsilencing viral methods and iPSCs made with retroviruses often maintain viral gene ex- Yamanaka, 2006 Blelloch et al, 2007;Yu et al, 2007;Brambrink et al, 2008Brambrink et al, 2008Stadtfeld et al, 2008b Free of genetic modification No genetic modification, still requires at least one factor to be transduced Okita et al, 2008Chang et al, 2009Soldner et al, 2009Stadtfeld et al, 2008cFusaki et al, 2009;Gonzalez et al, 2009Kaji et al, 2009Woltjen et al, 2009Bosnali and Edenhofer, 2008Huangfu et al, 2008aShi et al, 2008b;Ichida et al, 2009;Lyssiotis et al, 2009 pression thus limiting their utility (Maherali and Hochedlinger, 2008).…”
Section: Strategies For Ipsc Generationmentioning
confidence: 99%